Placental fibronectin staining is unaffected in pregnancies complicated by late‐onset intrauterine growth restriction and small for gestational age fetuses. Issue 2 (13th December 2019) - Fruscalzo, Arrigo; Londero, Ambrogio P.; Orsaria, Maria; Marzinotto, Stefania; Driul, Lorenza; Di Loreto, Carla; Mariuzzi, Laura
Abstract: Objective: To investigate the placental staining pattern of fibronectin, an extracellular matrix protein essential for trophoblastic invasion, in pre‐eclampsia and fetal growth restriction. Methods: This was a retrospective study conducted at the University of Udine, including the placentas of women with pre‐eclampsia and fetal growth restriction collected between January 1, 2001, and December 31, 2010. Fibronectin was evaluated in placental tissue micro‐array by immunohistochemistry, describing localization and intensity of staining. Results: The study included the placentas of 36 women with early‐onset (delivery <34 weeks of gestation) pre‐eclampsia; 6 with early‐onset HELLP syndrome; 17 with early‐onset intrauterine growth restriction (IUGR); 14 with late‐onset (delivery ≥34 weeks of gestation) pre‐eclampsia; 35 with late‐onset IUGR; 18 with small for gestational age (SGA) fetuses (birth weight <10th percentile); and 64 controls. Fibronectin was present both at the cell surface and in the cytoplasm. Cytoplasm staining intensity resulted higher in early forms of pregnancy‐related complications compared to controls, although this was statistically significant ( P <0.05) only for early‐onset pre‐eclampsia ( P =0.085 for HELLP syndrome; P =0.091 for IUGR). Also, late‐onset forms of pre‐eclampsia had stronger cytoplasmic and pericellular staining compared to controls ( P <0.05). Interestingly, staining of both late‐onset IUGR and SGA was comparable to controls. Conclusion: Fibronectin appeared to be unaffected in women with late‐onset IUGR and SGA fetuses, suggesting a peculiar common pathogenetic pattern in these conditions. Abstract : Placental fibronectin staining is not affected in late‐onset intrauterine growth restriction and small for gestational age pregnancies, suggesting a common pathogenetic pattern in these conditions.